Improving Students' Listening Skills and Vocabulary Mastery through Contextual Teaching and Learning by Using Online Learning - Yeni Ghonivita; John Pahamzah; Murti Ayu Wijayanti (Journal of English Language Teaching and Cultural Studies, 2021)
The aim of this research is to describe the process of improving the  students’ listening skill and vocabulary mastery through contextual teaching and learning (CTL) by using online learning at the eleventh grade of SMAN 1 Sajira. This study also attempts to find out the improvement of the students’ skill in listening and vocabulary mastery through contextual teaching and learning (CTL) by using online learning. The method used in this research was qualitative research method by implementing classroom action research (CAR). This research was conducted in three cycles actions in cycle I, cycle 2 and cycle 3. The result of the research is the use of contextual teaching and learning (CTL) by using online learning can improve the students’ listening skill and vocabulary mastery. The finding of the research are (1) the process of teaching and learning using CTL through online learning is conducted successfully in terms of the feeling of happiness and enthusiasm of the students, (2) there is an improvement of the students’ listening skill from 57.85 in pre-test became 81.11 in post-test. This study proves that English teacher can improve students’ listening and vocabulary mastery by optimizing the use of materials at school, and be creative in selecting, developing, and giving materials at class.